1998
DOI: 10.1177/154193129804200609
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Set Approach in the Quantification of Technical Support Service Quality

Abstract: Consumers' perceptions of service quality are highly qualitative as well as subjective. Individual variation exists in the meaning of “low,” “medium,” or “high” levels of service quality. A framework for quantifying the service quality dimension levels for technical support service is presented in the current study. Results are combined with the utility values of the dimension levels obtained through conjoint analysis. Customers' behavioral intentions subsequent to the quality of the technical support they exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The concept of fuzzy sets developed by Zadeh [1965] has been applied in various areas other than transportation engineering to assess user perception. For examples, evaluation of service quality [Rao et al, 1998], studies of operator safety in industrial engineering settings [McCauley-Bell and Badiru,1996], or applications for multiple attribute decision making processes [Ribeiro, 1996;Juang et al, 1992] are areas that have been studied using fuzzy sets. Fuzzy sets, where a more flexible sense of membership is possible, are classes with "un-sharp" and vague boundaries.…”
Section: Fuzzy Setsmentioning
confidence: 99%
“…The concept of fuzzy sets developed by Zadeh [1965] has been applied in various areas other than transportation engineering to assess user perception. For examples, evaluation of service quality [Rao et al, 1998], studies of operator safety in industrial engineering settings [McCauley-Bell and Badiru,1996], or applications for multiple attribute decision making processes [Ribeiro, 1996;Juang et al, 1992] are areas that have been studied using fuzzy sets. Fuzzy sets, where a more flexible sense of membership is possible, are classes with "un-sharp" and vague boundaries.…”
Section: Fuzzy Setsmentioning
confidence: 99%
“…Since Zadeh developed the concept in 1965 (11), fuzzy sets have been applied in various areas other than transportation engineering to assess user perception: the evaluation of service quality (12), the study of operator safety in industrial engineering settings (13), and applications for multiple-attribute decision-making processes (14,15). Fuzzy sets are classes with "unsharp," vague boundaries in which a flexible sense of membership is possible.…”
Section: Fuzzy Aggregation and Cultural Consensus Analysis Fuzzy Setsmentioning
confidence: 99%
“…Participants were asked to form an overall perception regarding the service qualities of 12 signalized intersections and to simultaneously evaluate their satisfaction with six service-element criteria for those intersections. Rao and colleagues conducted a survey that included an overall rating and specific perceptions of seven criteria about technical support service quality (12). In that study, these two perceptions were not compared, but the possibility of validating fuzzy aggregation output using these two perceptions was demonstrated.…”
Section: Validationmentioning
confidence: 99%
“…Meanwhile, there are several studies of service quality conducted by using fuzzy techniques. Rao et al developed a method for the quantification of consumer perceptions of technical support service quality in their 1998 study (2). They indicated that consumers' perceptions of service quality are qualitative and subjective.…”
Section: Literature Reviewmentioning
confidence: 99%